The Effect of Ankle Foot Orthosis' Design and Degree of Dorsiflexion on Achilles Tendon Biomechanics—Tendon Displacement, Lower Leg Muscle Activation, and Plantar Pressure During Walking - Fröberg, Åsa; Mårtensson, Mattias; Arndt, Anton (Frontiers in Sports and Active Living, 2020)
ABSTRACT Background: Following an Achilles tendon rupture, ankle foot orthoses (AFO) of different designs are used to protect the healing tendon. They are generally designed to protect against re-rupture by preventing undesired dorsiflexion and to prevent elongation by achieving plantarflexion in the ankle. There is limited knowledge of the biomechanical effects of different AFO designs and ankle angles on the tendon and lower leg muscles Hypothesis: The hypothesis was that non-uniform displacement in the Achilles tendon, lower leg muscle activity and plantar pressure distribution would be affected differently in different designs of AFO and by varying the degree of dorsiflexion limitation. Study Design: Controlled laboratory study Methods: Ultrasound of the Achilles tendon, EMG of the lower leg muscles and plantar pressure distribution were recorded in sixteen healthy subjects during walking on a treadmill unbraced and wearing three designs of AFO. Ultrasound speckle tracking was used to estimate motion within the tendon. The tested AFO designs were a rigid AFO and a dorsal brace used together with wedges and an AFO with an adjustable ankle angle restricting dorsiflexion to various degrees. Results: There were no significant differences in non-uniform tendon displacement or muscle activity between the different designs of AFO. For the rigid AFO and the adjustable AFO there was a significant reduction in non-uniform displacement within the tendon and soleus muscle activity as restriction in dorsiflexion increased. Conclusion: The degree of dorsiflexion allowed within an AFO had greater effects on Achilles tendon displacement patterns and muscle activity in the calf than differences in AFO design. AFO settings that allowed ankle dorsiflexion to neutral resulted in displacement patterns in the Achilles tendon and muscle activity in the lower leg which were close to those observed during unbraced walking.